Error Analysis and Compensation of a Three-degree-of-freedom Cervical Traction Rehabilitation Mechanisms - Hong Li; Qingfeng Wang; Xinyu Wang; Weixiao Lu (Jixie chuandong)
Based on the mechanism of human cervical traction rehabilitation and the characteristics of the cervical spine area that is precise and easily damaged， a 2-UPR/RPS three-degree-of-freedom cervical traction rehabilitation mechanism is proposed； the error analysis and compensation of this mechanism are carried out to avoid secondary damage to the cervical spine. Firstly， the error modeling is based on the closed vector method， and 11 important errors are identified according to the global error sensitivity； then， based on the given error range， global pose errors and local errors of the moving platform when z=600 mm and z=650 mm are analyzed； finally， based on the particle swarm algorithm， the optimal solutions for the four sets of error compensation are derived， and the joint experimental simulation analysis is carried out by Matlab and Adams software. The results show that the global pose error and the local error of vertical traction are reduced by 59.14% and 89.47% respectively， which effectively ensure the safety of the patient's cervical spine.